2009
DOI: 10.5194/acp-9-231-2009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of organosulfates in size-segregated rural fine aerosol

Abstract: Abstract.Organosulfates have recently come into the focus of organic aerosol research as potentially important components of water-soluble secondary organic aerosol (SOA) which now dominate tropospheric fine aerosol. Their presence has been confirmed by the identification of sulfate esters of abundant biogenic carbonyl compounds in both smog chamber and continental aerosol. However, none of the studies have been able to determine the mass contribution of organosulfates to SOA.In this paper, as possibly the ver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 41 publications
(48 reference statements)
5
60
1
1
Order By: Relevance
“…For the site of K-puszta, Hungary, and a 2003 summer period, which was very dry and warm (Ion et al, 2005), the calculations indicated that organosulfates could be responsible for 20% of the total PM 10 sulfur concentration and 30% of the PM 10 OM Surratt et al, 2008). Using a similar approach, it was estimated that organosulfates accounted for 6-14% of the total PM 2.5 sulfur concentration at the same site during summer 2006 (Lukács et al, 2009). …”
Section: Organosulfates and Nitrooxy Organosulfates From α-/β-Pinene Soamentioning
confidence: 77%
“…For the site of K-puszta, Hungary, and a 2003 summer period, which was very dry and warm (Ion et al, 2005), the calculations indicated that organosulfates could be responsible for 20% of the total PM 10 sulfur concentration and 30% of the PM 10 OM Surratt et al, 2008). Using a similar approach, it was estimated that organosulfates accounted for 6-14% of the total PM 2.5 sulfur concentration at the same site during summer 2006 (Lukács et al, 2009). …”
Section: Organosulfates and Nitrooxy Organosulfates From α-/β-Pinene Soamentioning
confidence: 77%
“…Although their prevalence in ambient aerosol remains unclear, further evidence for substantial OS contributions to SOA come from rainwater studies (21). Similar to ON, OS have been quantified as the difference between total particulate S and sulfate plus methylsulfonic acid (MSA); studies in rural Hungary estimated OS accounted for 6-14% of sulfate (22) and up to 30% of the total organic matter (23). OS fractions of this order would cause an error in the evaluation of acidity using nominally inorganic ions (24) and constitute a fraction of OA that is not accounted for in current models.…”
mentioning
confidence: 99%
“…Moreover, methanesulfonic acid (MSA) was found at the forest site, and its possible sources are discussed. MSA is formed by the photooxidation of dimethylsulfide (DMS) and is typically found in marinebiologically influenced aerosols; measurements of MSA in terrestrial regions are limited (e.g., Lukács et al, 2009). On the basis of these data sets, we discuss the relative importance of the forest floor in WSOC formation at a deciduous forest site.…”
Section: Introductionmentioning
confidence: 99%